Effect of Surface Shape and Content of Steel Fiber on Mechanical Properties of Concrete - Lijuan Zhang; Jun Zhao; Cunyuan Fan; Zhi Wang (Advances in Civil Engineering)
Steel fiber reinforced concrete (SFRC) has gained popularity in the last decades attributed to the improvement of brittleness and low tensile strength of concrete. This study investigates the effect of three shapes of steel fibers (straight, hooked end, and corrugated) with four contents (0.5%, 1%, 1.5%, and 2%) on the mechanical properties (compression, splitting tension, shear, and flexure) of concrete. Thirteen groups of concrete were prepared and investigated experimentally. Test results indicated that steel fiber had significant reinforcement on mechanical properties of concrete. When the steel fiber content increases from 0.5% to 2.0%, the compressive strengths increase about 4–24%, splitting tensile strengths increase about 33–122%, shear strengths increase about 31–79%, and flexural strengths increase about 25–111%. Corrugated steel fiber has the best reinforced effect on strength of SFRC, hooked end steel fiber takes the second place, and straight steel fiber is the least. Calculated formulas of compressive, splitting tensile, shear, and flexural strengths were established with consideration of the bonding properties between concrete and steel fiber. Influence factors of steel fiber αf and concrete matrix strength αc were put forward and determined by regression analysis of experimental data. Calculated results agree well with the experimental results.